Internet research tools: Discourse on the blogosphere - Ngeow, Karen; Ngeow, Y.M. (2010)
Internet-based and conventional research tools undeniably co-exist in a shared media space. Based on this premise, this paper discussed whether blogs can be viewed as a source for issues identification in a research study. The authors discuss blogging as indicator of social thought and practice, the increased credibility of bloggers’ discourse within cyber communities, and the reliability of blogs as an Internet research tool.